graphing problem

Jan 2010
142
0
i have this equation:

solve for x:
ln(x)+ln(x-3)=2

x=0, x=3

In addition:

graph f(x)=ln(x) and -f(x-3)+2 by using transformations. Explain the relationship between the solutions to the original equation and the points of intersection on your graph.

How do you graph -f(x-3)+2?

please help Idon't understand the problem. thanks!
 
Last edited:

earboth

MHF Hall of Honor
Jan 2006
5,854
2,553
Germany
i have this equation:

solve for x:
ln(x)+ln(x-3)=2

x>0 and x>3 <<<<<<<<< typo
Use the laws of logarithms:

\(\displaystyle \ln(x)+\ln(x-3)=2~\implies~\ln(x(x-3))=\ln(e^2)\)

Now use the logarithms as exponents to the base e. You'll get a quadratic equation. Keep in mind that this equation is only valid for x > 3

In addition:

graph f(x)=ln(x) and -f(x-3)+2 by using transformations. Explain the relationship between the solutions to the original equation and the points of intersection on your graph.

How do you graph -f(x-3)+2?

please help Idon't understand the problem. thanks!
1. Graph \(\displaystyle f(x)=\ln(x)\)

2. f(x-3) means the graph of f is translated by 3 units to the right.

3. -f(x-3) means the translated graph is refelcted about the x-axis.

4. -f(x-3) + 2 means the translated and reflected graph is translated by 2 units upwards.

5. The x-coordinate of the point of intersection is the solution to the equation above:

\(\displaystyle \ln(x)+\ln(x-3)=2~\implies~\underbrace{\ln(x)}_{f(x)}=\underbrace{-\ln(x-3)+2}_{-f(x-3)+2}\)
 
  • Like
Reactions: Anemori